Differences in Temporal Relapse Characteristics Between Affective and Non-affective Psychotic Disorders: Longitudinal Analysis - Immanuel, Sarah A.; Schrader, Geoff; Bidargaddi, Niranjan (Frontiers in Psychiatry, 2021)
Objective Multiple relapses over time is common in both affective and non-affective psychotic disorders. Characterizing the temporal nature of these relapses may be crucial to understanding the underlying neurobiology of relapse. Materials and Methods Anonymized records of patients with affective and non-affective psychotic disorders were collected from SA Mental Health Data Universe and retrospectively analyzed. To characterize the temporal characteristic of their relapses, a relapse trend score was computed using a symbolic series-based approach. A higher score suggests relapse follows a trend and a lower score suggests relapses are random. Regression models were built to investigate if this score was significantly different between affective and non-affective psychotic disorders. Results Logistic regression models showed a significant group difference in relapse trend score between the patient groups. For e.g., in patients who were hospitalized six or more times, relapse score in affective disorders were 2·6 times higher than non-affective psychotic disorders [OR 2.6, 95% CI (1·8-3.7), p<0.001]. Discussion The results imply that the odds of a patient with affective disorder exhibiting a regular trend in time to relapse were much higher than a patient with recurrent non-affective psychotic disorder. In other words, within recurrent non-affective psychosis group, time to relapse is random. Conclusion Temporal trends in relapse using time stamps along a mental health trajectory have not been investigated previously. This is a first step towards longitudinal trajectory-based approach to investigate relapse trend differences in mental health patients and further investigation may reflect differences in their underlying biological processes.